2022
DOI: 10.1021/acsnano.2c05029
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Temperature-Range Li–S Batteries Enabled by Thiodimolybdate [Mo2S12]2– as a Dual-Function Molecular Catalyst for Polysulfide Redox and Lithium Intercalation

Abstract: In lithium−sulfur batteries, a serious obstacle is the dissolution and diffusion of long-chain polysulfides, resulting in rapid capacity decay and low Coulombic efficiency. At present, a common practice is designing cathode materials to solve this problem, but this gives rise to reduced gravimetric and volumetric energy densities. Herein, we present a thiodimolybdate [Mo 2 S 12 ] 2− cluster as sulfur host material that can effectively confine the shuttling of polysulfides and contribute its own capacity in Li−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…Secondly, a new pair of peaks belonging to S B 0 appears after complete contact with Li 2 S. All of these changes in the S 2p spectrum point to the same information, namely, the oxidation of insoluble Li 2 S to soluble sulfides in the presence of MoSe 2 /CoSe 2 @NC. 51 To summarize these results, it can be found that Li 2 S is mainly oxidized by MoSe 2 in MoSe 2 /CoSe 2 @NC, which is in line with the conclusion of the above adsorption experiment. Finally, the Li 1s spectrum of the MoSe 2 /CoSe 2 @NC + Li 2 S sample is exhibited in Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Secondly, a new pair of peaks belonging to S B 0 appears after complete contact with Li 2 S. All of these changes in the S 2p spectrum point to the same information, namely, the oxidation of insoluble Li 2 S to soluble sulfides in the presence of MoSe 2 /CoSe 2 @NC. 51 To summarize these results, it can be found that Li 2 S is mainly oxidized by MoSe 2 in MoSe 2 /CoSe 2 @NC, which is in line with the conclusion of the above adsorption experiment. Finally, the Li 1s spectrum of the MoSe 2 /CoSe 2 @NC + Li 2 S sample is exhibited in Fig.…”
Section: Resultssupporting
confidence: 86%
“…3g). There are two new peaks appearing at 417 and 480 nm in the UV-vis spectrum of MoSe 2 /CoSe 2 @NC + Li 2 S, corresponding to S 4 51 To summarize these results, it can be found that Li 2 S is mainly oxidized by MoSe 2 in MoSe 2 / CoSe 2 @NC, which is in line with the conclusion of the above adsorption experiment. Finally, the Li 1s spectrum of the MoSe 2 /CoSe 2 @NC + Li 2 S sample is exhibited in Fig.…”
Section: Resultssupporting
confidence: 86%
“…112 In Li-S batteries, Ma et al discovered a symmetric binuclear molybdenum complex [Mo 2 S 12 ] 2À as a bidirectional electrocatalyst. 113 In the discharge process, [Mo 2 S 12 ] 2À clusters exhibit a dynamic Li-ion intercalation process similar to Mo 6 S 8 and evolve into Li 8 (Mo 2 S 12 ), which can enhance LiPS adsorption (Fig. 5a) and accelerate Li-ion migration.…”
Section: Intercalation-induced Transformationmentioning
confidence: 99%
“…Therefore, the researchers introduced nitrogen-doped carbon (N–C) with abundant pyrroline nitrogen and pyridine nitrogen structures to adsorb LiPSs Unfortunately, due to the low doping rate of heteroatoms, it is still difficult to overcome the serious capacity fading problem. So, the researchers introduced polar compounds (metal oxides, , nitrides, , sulfides, , etc.) that can form a certain chemical adsorption with polysulfides via the soft acid–soft base interaction between transition-metal cations and S 2– /S 2 2– , making them excellent chemisorption sites .…”
Section: Introductionmentioning
confidence: 99%